ANALISIS LIKUIDITAS, PERPUTARAN PERSEDIAAN DAN LEVERAGE TERHADAP PROFITABILITAS DI BURSA EFEK INDONESIA - Wang, Eddie; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2021)
Every entity that is established must have the goal of making a profit, increasing sales, and increasing the level of welfare of shareholders by obtaining profitability. The objective of this research is to determine the effect of liquidity, inventory turnover and Leverage on food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The population in this study were 31 companies listed on the Indonesia Stock Exchange in the food and beverage sub-sector manufacturing companies. In this study, a sample collection technique was used in the form of purposive sampling and there were 18 companies that had met the sample criteria determined by the researcher. The results of the research on the F test show that there is a significant influence on liquidity, inventory turnover, and Leverage simultaneously on profitability so that the regression model contained in this study is worthy of research. Meanwhile, the T test can be concluded that liquidity and inventory turnover have a significant effect on profitability and Leverage has no effect on profitability. And on the results of the coefficient of determination R2 obtained a percentage of 70.3% and 19.7% influenced by other factors not examined in this study.